RELATIONSHIP BETWEEN FAMILY SUPPORT AND DIABETIC FOOT CARE MANAGEMENT IN TYPE 2 DM PATIENTS AT THE KOTA UTARA PUBLIC HEALTH CENTER, GORONTALO CITY - Sulkifli, Putri Wulandari; Zainuddin, Zainuddin; Hiola, Dewi Suryaningsi (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Family support is needed for individuals to overcome the problems they face. Family support has an influence and has a positive impact on DM sufferers, so that with family support it can be a motivation and also a reminder for someone with DM in carrying out foot care management. The purpose of this study was to determine the relationship between family support and diabetic foot care management in Type 2 DM patients at the North City Health Center, Gorontalo City. This research method uses an analytical survey with a cross-sectional research design. The population of this study was patients with a diagnosis of DMT2 totaling 83 people. The sample consisted of 45 respondents with an accidental sampling technique. The results of the study were analyzed using the chi square statistical test. The results showed 30 respondents with low family support, 15 respondents with high family support, 26 respondents with poor foot care management, and 19 respondents with good foot care management. There is a relationship between family support and diabetic foot care management with a p value of 0.000 (<0.05). Conclusion: high family support can affect good foot care management.